A Select Few: Women and the National Research Council of Canada, 1916-1991 - Gosztonyi Ainley, Marianne; Millar, Catherine (Scientia Canadensis, 1991)
AbstractThis paper explores the interrelationship of women and the National Research Council of Canada during the 1916-1991 period. Although women received 14% of the NRC fellowships and bursaries before 1931, they fared less well during and after the Depression. Based on information obtained from primary and secondary written sources as well as from interviews with both women and men employed by the NRC, the paper traces changing trends in employment practices and improved research opportunities for women scientists at the NRC.